Nilai Hematologi Rusa Sambar (Cervus unicolor) yang ditangkarkan - G. Semiadi; R Wilson; P. D. Muir; T. N. Barry (Media Veteriner, 1995)
Nine tame young (10-14 monts of age) housed sambar, consided of 5 stags and 4 hinds, were blood sampled in May 1992 (late autum) and september 1992 (early spring) using physical restraint without sedation. In May 1992, four semidomestical adult sambar stags in hard antler; managed at pasture were sedated using a mixture of xylazine hydrochlorine (Rompun, Bayer, NZ) and fentanyl citrate-azaperone (Fentas, Ethnor Pty.Ltd.Nort Ryde, Australia), at a ratio of 3:1. administrated by traquillizer dart (Paxarms Ltd, Timaru, NZ) and were blood sampled. All samples were analyzed for standart haematological analysis (Hill et al.1992).